Assessing the state of infection prevention and control in cameroon: a cross-sectional workshop evaluation using socioecological models - Boris Arnaud Kouomogne Nteungue; Erick Tandi; Jeffrey Campbell; Chanceline Bilounga Ndongo; Bissouma-Ledjou Tania; Alphonse Acho; Dieudonnée Reine Ndougou; Reverien Habimana; Ambomo Sylvie Myriam; Bertolt Brecht Kouam Nteungue; Oyono Yannick; Louis Joss Bitang; et al. (Elsevier, 2024)
Summary: Objectives: Infection prevention and control (IPC) contributes to the reduction of healthcare associated infections. Notwithstanding the global attention with available guidelines and tools, low- and middle-income countries (LMICs) still struggle to put into place effective IPC programmes. Here, we use a socioecological approach to summarize the findings of a recent workshop on the implementation of IPC activities in Cameroon. Study design: We conducted a cross-sectional study on the assessment of the IPC in Cameroon. Methods: Experts and key stakeholders involved in IPC in Cameroon evaluated the implementation of infection prevention and control during a 4-day workshop. Detailed summaries of workshop discussions and recommendations were created. Data were clustered into themes guided by the WHO core component of IPC. Results were analyzed using the socioecological model of Bronfenbrenner, McLeroy and the theory of Grol and Wensing on successful implementation of practices in healthcare settings. Results: Cameroon does not have an effective IPC programme in place but has developed some areas of the World Health Organization (WHO) IPC core components across the guideline level, the individual level, the organizational level, and the political level. Conclusion: Cameroon is still far from the norms and standards laid out by the WHO. The evidence generated from the current analysis should contribute to improve policies and strategies towards an effective IPC programme in Cameroon and other LMICs.